Development of Cell Transmission Model for Traffic Signal Coordination - Lye Yoke Kei; Dr. Susilawati (Journal of Infrastructure & Facility Asset Management, 2020)
This research aims to develop a macroscopic traffic model to estimate delay at signalized intersections by considering queue forming and dissipation in the presence of pre-timed signal. Cell Transmission Model (CTM) was set up with basic traffic input parameters to estimate delay and level of service (LOS) and the results are compared to computational analysis run by SIDRA (Signalized and Unsignalized Intersection Design and Research Aid) software. To optimize the traffic flow condition, traffic signal coordination is carried. It was found that optimized traffic signal setting reduces delay by 25.5% and 17% in Intersection A and Intersection B after a second run by CTM.